PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN CONSUMER GOODS YANG TELAH GO PUBLIC DI BURSA EFEK INDONESIA - Setyaningsih Setyaningsih; Salamatun Asakdiyah (Jurnal Fokus Manajemen Bisnis, 2013)
This research aimed to examine the effect of the financial performance of hte stock price. Company that the sample is a consumer goods company that has gone public listed on the Indonesia Stock Exchange 2006-2010 period by 30 companies. The dependent variable used is the stock price while the independent variable is Return On Equity (ROE), Net Profit Margin (NPM), Debt ti Equity Ratio (DER) and Earning Per Share (EPS). In this study using a multiple regression test, t test, and classical assumption. Assessement of the effect of independent variable on the dependent variable was partially and using the classical assumption test for normality, multicollinearity, heteroscedasticity, and autocorrelation. The research using multiple regression test showed that the Net Profit Margin (NPM) and Debt to Equity Ratio (DER) has a probability of 0.0715, respectively, and 0.4396 ata a significance level of 0.05 (5%), both variables no significant effect on stock price. While Return on Equity (ROE) and Earning Per Share (EPS) have respective probabilities 0.0000 and 0.0000 at tha significant level of 0.05 (5%), than two variables significant effect on stock prices because probability of 0,001 < 0.05. The coefficient of determination (R square is equal to 0.847. this means that the ability of the four independent variables explained 84.7% of the dependent variable. And of the results of the classical assumption states that the problem of test for normality and heteroscedasticity test, whereas the multicollinearity test and autocorrelation test no problems.